Models and Implementation of Curriculum Development in Schools - Mahfud Heru Fatoni; Baron Santoso; Hamid Syarifuddin; Hanif Hanani (International Journal of Educatio Elementaria and Psychologia, 2024)
Curriculum development cannot be separated from various aspects that influence it. Various curriculum models have been developed by curriculum, education and psychology experts. This research aims to find a model for curriculum development in schools and its implementation. In this article, the author uses library research or what could be called qualitative research which obtains data from appropriate journals, articles and books. The research results found that in developing the curriculum, teachers can choose several models including the Tyler Model, Administrative Model, Grass Roots Approach Model, Demonstration Model, Beauchamp's System Model or Beauchamp Model, Roger's Model, Problem Solving Model and Taba's Inverted Model. The procedures for curriculum development include curriculum planning, curriculum organization, staffing and curriculum control. Meanwhile, curriculum implementation is the process of applying ideas, concepts, policies, in the form of practical actions, so that it has an impact, both in the form of changes in knowledge, skills, as well as students' values and attitudes. The success of curriculum implementation is also determined by communication about the implementation plan and the support of all resources in the implementation.